Educational intervention on the harmful effects of tobacco in smoking patients. Medical Clinic 33. Policlínico Luis Augusto Turcios Lima - Capote Serrano, Rigoberto; Ramírez Guzmán, Sandra (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: smoking is currently a social phenomenon that affects all sectors of the population and represents one of the major problems faced by health authorities. Cuba is among the first three countries in the world in per capita consumption of cigarettes and tobacco. Objective: to evaluate an educational intervention on the harmful effects of tobacco in the smoker patients studied. Method: An action research was carried out in clinic 33 belonging to the University Polyclinic "Luis Augusto Turcios Lima", Pinar del Río, during the period from September 2020 to June 2022. Qualitative and quantitative variables were studied. Results: in the sample there was a predominance of smokers between 20 and 59 years of age, male sex and pre-university school level.  In all patients there was a significant increase in the level of knowledge about the harmful effects of smoking and the benefits of quitting. The number of cigarettes smoked per day was significantly modified by the educational intervention and 5% of the patients quit smoking. The factor that most influenced the maintenance of the habit was the social factor. Conclusions: the educational intervention succeeded in raising the patients' level of knowledge about smoking and in reducing, although to a lesser extent, its prevalence in the population studied